If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15(3 + x) + -6(3x + -1) + -7(1 + -1x) = 3(2 + -3x) + -1 (3 * 15 + x * 15) + -6(3x + -1) + -7(1 + -1x) = 3(2 + -3x) + -1 (45 + 15x) + -6(3x + -1) + -7(1 + -1x) = 3(2 + -3x) + -1 Reorder the terms: 45 + 15x + -6(-1 + 3x) + -7(1 + -1x) = 3(2 + -3x) + -1 45 + 15x + (-1 * -6 + 3x * -6) + -7(1 + -1x) = 3(2 + -3x) + -1 45 + 15x + (6 + -18x) + -7(1 + -1x) = 3(2 + -3x) + -1 45 + 15x + 6 + -18x + (1 * -7 + -1x * -7) = 3(2 + -3x) + -1 45 + 15x + 6 + -18x + (-7 + 7x) = 3(2 + -3x) + -1 Reorder the terms: 45 + 6 + -7 + 15x + -18x + 7x = 3(2 + -3x) + -1 Combine like terms: 45 + 6 = 51 51 + -7 + 15x + -18x + 7x = 3(2 + -3x) + -1 Combine like terms: 51 + -7 = 44 44 + 15x + -18x + 7x = 3(2 + -3x) + -1 Combine like terms: 15x + -18x = -3x 44 + -3x + 7x = 3(2 + -3x) + -1 Combine like terms: -3x + 7x = 4x 44 + 4x = 3(2 + -3x) + -1 44 + 4x = (2 * 3 + -3x * 3) + -1 44 + 4x = (6 + -9x) + -1 Reorder the terms: 44 + 4x = 6 + -1 + -9x Combine like terms: 6 + -1 = 5 44 + 4x = 5 + -9x Solving 44 + 4x = 5 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 44 + 4x + 9x = 5 + -9x + 9x Combine like terms: 4x + 9x = 13x 44 + 13x = 5 + -9x + 9x Combine like terms: -9x + 9x = 0 44 + 13x = 5 + 0 44 + 13x = 5 Add '-44' to each side of the equation. 44 + -44 + 13x = 5 + -44 Combine like terms: 44 + -44 = 0 0 + 13x = 5 + -44 13x = 5 + -44 Combine like terms: 5 + -44 = -39 13x = -39 Divide each side by '13'. x = -3 Simplifying x = -3
| 4(3.2+k)=8.2 | | 3(x+3)+2(2x-4)=12(2x-7) | | k+(-13)=37 | | 300x+1590=x-818 | | -4x+21=2x+36 | | 6x-12x=0 | | 2x-10=24 | | 1-4xy+4x^2-y^2=0 | | 7x+10=6x | | -126-11x=78-5x | | 5x=3x+40 | | 2x-4=5x+40 | | 4+-9=-4t+7 | | (8+w)(5w-1)=0 | | -39-6x=66-13x | | 3x(11-7)+8= | | 10x-26=13x+61 | | -2x+60=-4x+20 | | 5x+3x+40=180 | | 12x+3=-14x+8 | | -3x-19=11-4x | | 3n-5/6=n+5/6 | | 2-4(y+6)=y+6(y-3)+8 | | 0.5n=3.5 | | 3x=16.5 | | -110-9x=76-3x | | -4w=-72 | | n-11=4+4 | | 6(x-3)=5x+10 | | 78=5x+3 | | 6(x-1)-2+2x=8x+4 | | -x-240=90+9x |